Behavioral healthcare organizations' experiences related to use of telehealth as a result of the COVID-19 pandemic: an exploratory study - Abby Kisicki; Sara Becker; Michael Chaple; David H. Gustafson; Bryan J. Hartzler; Nora Jacobson; Ann A. Murphy; Stephanie Tapscott; Todd Molfenter (BMC, 2022)
Abstract Background Due to the COVID-19 pandemic, healthcare providers were forced to shift many services quickly from in-person to virtual, including substance use disorder (SUD) and mental health (MH) treatment services. This led to a sharp increase in telehealth services, with health systems seeing patients virtually at hundreds of times the rate as before the onset of the COVID-19 pandemic. By analyzing qualitative data about SUD and MH care organizations' experiences using telehealth, this study aims to elucidate emergent themes related to telehealth use by the front-line behavioral health workforce. Methods This study uses qualitative data from large-scale web surveys distributed to SUD and MH organizations between May and August 2020. At the end of these surveys, the following question was posed in free-response form: "Is there anything else you would like to say about use of telehealth during or after the COVID-19 pandemic?" Respondents were asked to answer on behalf of their organizations. The 391 responses to this question were analyzed for emergent themes using a conventional approach to content analysis. Results Three major themes emerged: COVID-specific experiences with telehealth, general experiences with telehealth, and recommendations to continue telehealth delivery. Convenience, access to new populations, and lack of commute were frequently cited advantages of telehealth, while perceived ineffectiveness of and limited access to technology were frequently cited disadvantages. Also commonly mentioned was the relaxation of reimbursement regulations. Respondents supported continuation of relaxed regulations, increased institutional support, and using a combination of telehealth and in-person care in their practices. Conclusions This study advanced our knowledge of how the behavioral health workforce experiences telehealth delivery. Further longitudinal research comparing treatment outcomes of those receiving in-person and virtual services will be necessary to undergird organizations' financial support, and perhaps also legislative support, for virtual SUD and MH services.